Building Brand Love for Travelers Through Accessibility, Destination Image, and Emotional Energy in Individuals at Laut Tawar Lake - Nasib; Syaifuddin; Rusiadi (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
Deep goals study This is for know directly influences accessibility, destination image, and emotional energy in individuals towards brand love. Type of research that is study quantitative. The population is previous tourists who have visited Lake Laut Tawar for at least two visits. Deep sample study This was taken with an accidental sampling technique of 100 tourists. Data was collected with a compiled questionnaire based on each indicator variable research. Analysis results study show that accessibility, destination image, and emotional energy in individuals direct influential significance towards brand love. The most dominant variable influencing tourist brand love is accessibility compared with destination image and emotional energy in individuals.